Spectral Properties of Chloride Salt‐Bearing Assemblages: Implications for Detection Limits of Minor Phases in Chloride‐Bearing Deposits on Mars. Issue 2 (1st February 2019) - Ye, Cheng; Glotch, Timothy D.
Abstract: Chloride salt‐bearing deposits have been identified throughout the southern highlands of Mars and have been suggested to be two component mixtures of anhydrous chloride salt and regional basaltic regolith. On Earth, chlorides typically occur as evaporite salts associated with other evaporite minerals such as carbonate and sulfate, and chemical weathering products like clays. In this laboratory study, we document the visible/near‐infrared reflectance and midinfrared emissivity spectral characteristics of a series of chloride salt‐bearing mineral assemblages. Our data show that the spectral features of various powder mixtures change systematically with variable additional mineral concentrations and particle sizes. Specifically, small amounts of calcite, gypsum, or nontronite have a relatively large effect on the bulk spectral properties of halite/labradorite mixtures making them easily distinguishable from two‐component halite/labradorite mixtures. This fundamental laboratory work suggests that additional minor phases could only be present at no more than 1–5 wt% in Martian chloride salt‐bearing deposits. Plain Language Summary: Chloride salt‐bearing deposits have been identified throughout the southern highlands of Mars. Since these deposits could form through the evaporation of brines, they can indicate that water once was widespread and could remain over a long time in Martian ancient history. Chloride salt deposits are intriguing since they may be good at preserving past Martian life. Unlike evaporite salt deposits on Earth, which are usually a set of evaporite minerals, chloride salt‐bearing deposits on Mars are isolated chloride salt mixed with regional basaltic soil. In this work, we use visible/near‐infrared and midinfrared spectroscopy to characterize spectral features of a series of chloride salt‐bearing mineral assemblages. We suggest that additional minor phases could only be present at very low abundances in Martian chloride salt‐bearing deposits. Key Points: We characterized visible/near‐infrared reflectance and midinfrared emissivity spectra of chloride salt‐bearing assemblages We constrained detection limits of minor phase that could be present in chloride‐bearing assemblages We suggested that additional minor phases could only be present at very low abundances in Martian chloride salt‐bearing deposits